Can Baumol's model of unbalanced growth contribute to explaining the secular rise in health care expenditure? An alternative test - Jochen Hartwig (ETH Zurich, KOF Swiss Economic Institute, 2007)
In a recent paper I argued that Baumol's (1967) model of unbalanced growth offers a ready explanation for the observed secular rise in health care expenditure (HCE) in rich countries (HARTWIG 2006). Baumol's model implies that HCE is driven by wage increases in excess of productivity growth. I tested this hypothesis empirically using data from a panel of 19 OECD countries and found robust evidence in favor of Baumol's theory. An alternative way to test Baumol's theory is to check whether its implication that variations in the relative price of medical care contribute significantly to explaining variations in health expenditure in the same direction has an empirical grounding. Earlier studies, although mostly not in an explicit attempt to test Baumol's theory, have occasionally rejected this hypothesis. Despite poor data quality of the available medical price indices, I perform the alternative test using data for nine OECD countries. My findings suggest that the relative price of medical care is in fact a statistically significant explanatory variable for health expenditure, thus lending support to Baumol's theory.
Keywords: C12; C23; E31; I10; O41; 330; Rising health expenditure; unbalanced growth; medical care prices; OECD panel; Ungleichgewichtiges Wachstum; Gesundheitskosten; Arbeitsproduktivität; Lohnniveau; OECD-Staaten